Mental Practice Ability Among Stroke Survivors: Investigation of Gender and Age - Storm, Vera; Utesch, Till (Frontiers in Psychology, 2019)
Background: Mental practice refers to the imaginary representation of a motor action. Mental practice interventions are frequently used among stroke survivors to improve motor function. Individual characteristics that may determine whether a person is able to mentally perform a specific movement have been mainly spared in research. Aims: The aim of the present study is to examine whether gender and age are related to mental practice ability. Methods: The study has a cross-sectional design. Data collection was done via self-report questionnaires on mental practice ability, sociodemographic information, and perceived stroke impact. Data analysis was conducted in R using descriptive statistics and regression analysis. N = 44 stroke survivors (M = 65.8 years, SD = 11.4, range 48–88), n = 19 of which were female were recruited in two German neurologic rehabilitation facilities. Results: Age (β = −0.13, p = 0.057) and gender (β = 0.17, p = 0.260) were not associated with mental practice ability, when controlling for time since stroke and perceived stroke impact (Stroke Impact Scale). Perceived stroke impact was significantly related to mental practice ability (β = 0.44, p = 0.004). Those who reported less stroke impact showed better mental practice ability. Conclusion: Mental practice ability may be preserved in stroke patients, irrespective of age and gender. We report cross-sectional data on mental practice ability in this study, thus the direction of the relationship between mental practice ability and perceived stroke impact is of interest. Future studies should aim at using a longitudinal design and bigger sample sizes.